Personality and Situational Effects on Leader Behavior - Green, Stephen G.; Nebeker, Delbert M.; Boni, Melania (Academy of Management Journal, 1976)
This paper examines Fiedler's proposed relationship between leader behavior and two variables related to the Contingency Model. The evidence strongly suggests that under stress in a threatening situation, leaders with high Least Prefered Coworker (LPC) scores are more interpersonally oriented while low LPC leaders are more task oriented.